Development of nickel-based catalysts supported on gasification slag for steam reforming of tar compounds - Chia, Victor Wei Keat (2018)
One of the hindrances towards syngas utilisation is the high content of tar compounds which fouls on equipment upon syngas cooling causing pipe clogging and corrosion. Catalytic steam reforming is a promising technology for tar decomposition. However, commercial Ni catalysts are usually only used in fixed bed reactor due to the low attrition resistance. Studies showed that supports play an important role in its resistance to attrition and deactivation. This study explores the utilization of gasification slag, the by-product of MSW gasification with high mechanical strength, as a support for a nickel-based reforming catalyst to be used on fluidzed bed. Two different approaches for the preparation of catalyst were investigated, namely, HF etching of slag and addition of aluminium hydroxide to slag. Modifications of the supports for nickel catalysts were adopted to create surface area and porosity (different durations of HF solution etching) and to provide higher conversion efficiency (mixing of supports with porous aluminium hydroxide). Fluidization tests and characterizations for the catalysts synthesized were also conducted to study the attrition resistance and deactivation of the catalysts. Results from this study showed that by treating the slags with HF solution for 2.5 min, and mixing them with 20% of aluminium hydroxide by mass, the synthesized catalyst can achieve a lower naphthalene conversion of around 64.8% and a similar CO/CO2 selectivity while giving a better attrition resistance as compared to commercial Ni catalysts. Further studies can be conducted to explore different modifications of slag, at different conditions and longer durations of steam reforming to examine the performance and deactivation of the synthesized catalysts using slags as the supports.